2014
DOI: 10.1080/00981389.2014.884041
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of Social Workers in Home-Based Primary Care

Abstract: The growing homebound population has many complex biomedical and psychosocial needs and requires a team based approach to care (Smith, Ornstein, Soriano, Muller, & Boal, 2006). The [XX] Visiting Doctors Program (MSVD), a large interdisciplinary home based primary care program in [XX], has a vibrant social work program that is integrated into the routine care of homebound patients. We describe the assessment process used by MSVD social workers, highlight examples of successful social work care, and discuss why … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
41
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 28 publications
3
41
0
7
Order By: Relevance
“…Participants wanted information about resources and eligibility for those resources, responsibilities of medical professionals, and ICH symptoms. Discharge planning services were not solely meeting the needs of most clients and caregivers in this study (Judd & Sheffield, 2010; Reckrey et al, 2014). Therefore, in order to decrease readmissions among clients with ICH, social workers may need time to provide additional support outside of discharge planning, especially related to clients’ emotions and advocacy.…”
Section: Discussion and Applications To Social Workmentioning
confidence: 80%
See 4 more Smart Citations
“…Participants wanted information about resources and eligibility for those resources, responsibilities of medical professionals, and ICH symptoms. Discharge planning services were not solely meeting the needs of most clients and caregivers in this study (Judd & Sheffield, 2010; Reckrey et al, 2014). Therefore, in order to decrease readmissions among clients with ICH, social workers may need time to provide additional support outside of discharge planning, especially related to clients’ emotions and advocacy.…”
Section: Discussion and Applications To Social Workmentioning
confidence: 80%
“…However, little attention is paid to psychological distress experienced by clients and caregivers specific to discharge planning and making medical decisions. Reckrey and colleagues (2014) found that hospital social workers spent about one-fourth of their time on caregiver coping and other issues that seemed related to easing anxiety during discharge planning, such as assistance in moving. However, other research also found that it is typical for social workers to only have a single session with a client (Gibbons & Plath, 2006).…”
Section: Discussion and Applications To Social Workmentioning
confidence: 99%
See 3 more Smart Citations